Brazilian version of the Rivermead Post-Concussion Symptoms Questionnaire - Nagumo, Marcia Mitie; Ferretti-Rebustini, Renata Eloah de Lucena; Balbinotti, Marcos Alencar Abaide; Silva, Daniele Vieira da; Hayashi, Cintya Yukie; Paiva, Wellingson Silva; Teixeira, Manoel Jacobsen; Amorim, Robson Luis Oliveira de (Arquivos de Neuro-Psiquiatria, 2021)
Background: After a traumatic brain injury, post-concussion symptoms are commonly reported by patients. Although common, these symptoms are difficult to diagnose and recognize. To date, no instruments evaluating post-concussion symptoms have been culturally translated or adapted to the Brazilian context. Objective: To culturally adapt the Rivermead Post-Concussion Symptoms Questionnaire for use in Brazilian Portuguese. Methods: Cross-cultural adaptation was done in five steps: translation, synthesis of translations, back-translation, evaluation by two expert committees and two pretests among adults in a target population. Results: The semantic, idiomatic, cultural and experimental aspects of the adaptation were considered adequate. The content validity coefficient of the items regarding language clarity, pratical pertinence, relevance and dimensionality were considered adequate for evaluating the desired latent variable. Both pretests demonstrated that the instrument had satisfactory acceptability. Conclusion: The Brazilian version, named Questionário Rivermead de Sintomas pós Concussionais (RPQ-Br), has been adapted, and is ready for use in the Brazilian context.
Keywords: Brain Injuries, Traumatic; Post-Concussion Syndrome; Translating; Psychometrics